Pengembangan e-modul berbasis PBL untuk meningkatkan kemampuan analisis dan rasa ingin tahu siswa - Melati Astria Jayanti; Kartika Ratna Pertiwi (University of Muhammadiyah Malang, 2023)
Coordination system content in Biology learning is still considered difficult because the material is broad, complex, and difficult to visualize in real life. Problem based learning could become an alternative learning model to train students' problem-based analysis skills and curiosity. This study aims to develop a PBL-based e-module of coordination system topic in the form of a website and to determine the effectiveness of the developed e-module to improve the analysis skills and curiosity of high school students at grade XI. The development of e-module used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Validity of e-modules was done by media and content experts. The trial of the developed e-module was conducted to XII grade students of SMA 1 Cangkringan. The research subjects were students of class XI SMA 1 Cangkringan, who were selected with purposive sampling technique. They are divided into experimental and control groups. Analysis ability was measured with essay test, while curiosity was measured with adapted the curiosity non-test instrument. Data were analyzed using Mann Whitney test. The results showed that 1) the developed e-module was feasible to use based on the assessment from material and media experts, and responses from teacher and students, 2) PBL-based e-module in the form of a website is effective in improving students' analytical skills (p=0.024) and curiosity (p=0.000). It can be concluded that PBL-based e-module can improve students' analytical skills and curiosity.